The Effectiveness of the Animated Video-Based Tarl Model on Digital Literacy Skills In Elementary Schools - Arfan, Arfan; Syarifudin, Syarifudin; Ahyar, Ahyar (Journal of Educational Sciences, 2025)
This study aims to analyze the effectiveness of the Teaching at the Right Level (TaRL) model based on animated videos in improving digital literacy skills of elementary school students. The research used a quasi-experimental method with a Non-Equivalent Control Group Design involving 28 grade V students of SDN Sari Kalampa, divided into experimental and control groups. The experimental group learned through the TaRL model with animated video integration, while the control group used conventional learning. Data were collected through pretest, posttest, observation, interview, and documentation, and analyzed using SPSS, JAMOVI, Rasch MINISTEP, SMARTPLS 4, and NVIVO. The results showed significant improvement in the experimental group, with an average posttest score of 84.29 and N-Gain of 0.69 (high category), compared to the control group with 65.36 and N-Gain 0.34 (medium). All five indicators of digital literacy increased, with the highest improvement in evaluating digital information (N-Gain = 0.74). These findings indicate that the animated video-based TaRL model is effective in improving students' critical thinking, ethical awareness, content creation, and collaboration. Thus, the model can be recommended as an innovative pedagogical strategy to support 21 st-century learning in primary schools.